Politics in the Roman Republic: Perspectives from Niebuhr to Gelzer - Barber, Cary Michael (Brill Research Perspectives in Humanities and Social Sciences., 2022)
B. G. Niebuhr, the founder of 'modern history', exerts an enduring influence; even in death, Goethe once claimed, '[Niebuhr] still walks around and works'. Today, Niebuhr is a humbler phantom, rarely invoked and largely forgotten. Similar fates await the shades of Theodor Mommsen, Friedrich Münzer, and Matthias Gelzer. Yet, each demands reconsideration and revitalization. Their texts remain foundational, constituting the conceptual and methodological core of Republican political studies. Politics in the Roman Republic (re)presents the first critical, comprehensive, Anglophone survey of these scholars' influence. Its innovative reassessments dispel deep-seated misconceptions and emphasize relevance. The work's unique (re)interpretations render it essential reading for any student of Rome: specialist and non-specialist alike.